S103 A decrease in elafin due to proteolytic cleavage may contribute to alveolar inflammation in patients with ALI. (16th November 2010) - Kerrin, A; O'Kane, C; Shyamsundar, M; Craig, T; Taggart, C C; McAuley, D F
Abstract : Introduction: Unregulated protease activity is implicated in the pathogenesis of acute lung injury (ALI). Elafin is a potent serine protease inhibitor produced by epithelial and inflammatory cells with anti-inflammatory actions. Aim: To assess the temporal changes in elafin concentration in patients with ALI and test the hypothesis that a decrease in elafin levels due to proteolytic degradation may drive pulmonary inflammation. Methods: Patients with ALI within 48 h of onset of ALI (n=37), day 3 (n=19) and day 7 (n=9) as well as five healthy volunteers underwent bronchoalveolar lavage (BAL). Elafin was measured by ELISA. To determine whether elafin was susceptible to proteolytic cleavage, western blot analysis of recombinant elafin was incubated with BAL±protease inhibitors. Alveolar macrophages from healthy volunteers were isolated and pre-treated with 10 μg/ml elafin for 1 h, followed by 24 h stimulation with 100 ng/ml LPS. IL-8 was measured in supernatants by ELISA. Results: Elafin was significantly increased at the onset of ALI compared to healthy volunteers (39±5 ng/ml vs 0.5±0.1 ng/ml; p<0.0004). Elafin levels fell significantly by day seven compared to baseline (16±4 ng/ml vs 39±5 ng/ml; p=0.02). Incubation of exogenous elafin with day 7 ALI BAL revealed that elafin underwent proteolytic cleavage (Abstract S103 Figure 1A ). In contrast, proteolytic cleavage was not observed following incubation of exogenous elafin with day 0 ALI or healthy volunteer BAL. Pre-incubation of Day 7 ALI BAL with TLCK and Pefabloc abrogated this degradation suggesting that a trypsin-like protease may be responsible for the cleavage of elafin (Abstract S103 Figure 1A ). Pretreatment of alveolar macrophages with elafin decreased LPS induced IL-8 production (Abstract S103 Figure 1B ). Conclusion: Elafin concentrations fall in the pulmonary compartment over the course of ALI. This decrease was found to be due to proteolytic degradation. Furthermore elafin decreases LPS stimulated IL-8 release from alveolar macrophages. Together these data suggest loss of elafin in the alveolar airspace may result in dysregulated inflammation in ALI. Elafin augmentation may be a potential therapeutic strategy in ALI.